The interaction of CD300lf and ceramide reduces the development of periodontitis by inhibiting osteoclast differentiation. (25th October 2022) - Hu, Qiannan; Yang, Lisa; Shan, Zhongyan; Wen, Shuqiong; Lu, Huanzi; Zou, Zhaolei; Guo, Junyi; Liu, Xiangqi; Xie, Wenqiang; Cao, Yang; Wang, Zhi; Yang, Le; et al.
Abstract: Aim: The regulation of osteoclasts (OCs) by inhibitory immunoreceptors maintains bone homeostasis and is considered an important determinant of the extent of periodontal pathology. The aim of this study was to investigate the role of the inhibitory immunoreceptor CD300lf and its ligand ceramide in osteoclastogenesis in periodontitis. Materials and Methods: The expression of CD300lf was measured in vitro and in a ligature‐induced periodontitis model. The effect of CD300lf ablation on osteoclastogenesis was examined in ligature‐retained and ligature removal periodontitis models. The effect of ceramide, the ligand of CD300lf, was examined in osteoclastogenesis in vitro and in vivo by smearing 20 μg of ceramide dissolved in carboxymethylcellulose on teeth and gingiva every other day in an experimental periodontitis model and ligature removal model. Results: CD300lf expression was downregulated during osteoclastogenesis. Ablation of CD300lf in the ligature‐induced periodontitis model increased the number of OCs and exacerbated bone damage. Bone resorption caused by CD300lf ablation was reversible following ligature removal. CD300lf‐ceramide binding suppressed osteoclastogenesis in vitro and inhibited alveolar bone loss in a mouse periodontitis model. Conclusions: Our findings reveal that CD300lf‐ceramide binding plays a critical negative role in alveolar bone loss in periodontitis by inhibiting OCs differentiation.